Pengaruh E-Service Quality dan Customer Satisfaction Terhadap Customer Loyalty pada Konsumen Grab di Fisip Universitas Hang Tuah Surabaya - Giovanni, Lawrenzia; Winarto (Journal Of Accounting and Business, 2023)
Customer loyalty is an important aspect for service/product provider companies because it is one of their valuable asset. There are also several aspects related to customer loyalty such as e-service quality and customer satisfaction. This study aims to examine the effect of e-service quality and customer satisfaction on customer loyalty among Grab consumers at FISIP Hang Tuah University, Surabaya. This research was conducted on Grab consumers at the Faculty of Social and Political Sciences, Hang Tuah University, Surabaya. There are subjects taken using a purposive sampling technique totaling 65 people. The data analysis technique used is multiple linear regression. Based on the results of hypothesis testing found a significant value of 0.000, sig <0.05, otherwise the correlation coefficient value is 40.705, which means that the t count is greater at N = 65 and a significance level of 5%, namely 2.75 (40.705 > 2.75) The result shows that the e-service quality and customer satisfaction variables have a positive and significant effect on customer loyalty. This means that the higher the service quality, the higher the customer loyalty. E-service quality and customer satisfaction have an effect of 55% on customer loyalty, the remaining 45% is influenced by other factors.